Milk quota expiry impacts and sensitivity analyses using the CAPSIM model - Heinz Peter Witzke; Axel Tonini (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2009)
Various scenarios for an expiry of European Union milk quotas are analysed with the Common Agricultural Policy SIMulation (CAPSIM) model. This comparative-static, partial equilibrium modelling tool covering the whole of agriculture for all EU member states has been disaggregated to represent nine secondary dairy products. Impacts are compared to a reference run where the 2003 Common Agricultural Policy Reform is projected into the future. The main milk quota expiry scenario is for 2020. Key results are that milk production would increase by 3.0% in EU-27 whereas milk prices would drop by 7.2%. The resulting decline in butter prices is shown to be larger if EU authorities cannot rely on export subsidies for market management. The regional pattern of impacts is strongly determined by the specification of quota rents. Furthermore, details of intra EU price transmission are shown to influence the differences between Member States. An applied welfare analysis of the main expiry scenario gives a significant redistribution from EU-27 farmers and much less from taxpayers to dairies and final consumers. The estimated small positive overall welfare gain would increase in a situation without export subsidies. – – Verschiedene Szenarien zur Abschaffung der EU-Milchquoten wurden mit dem 'Common Agricultural Policy SIMulation' (CAPSIM) Modell untersucht. Dieses komparativ-statische partielle Gleichgewichtsmodell wurde im Milchsektor erheblich disaggregiert (neun Verarbeitungsprodukte). Der Referenzlauf beinhaltet eine Beibehaltung der derzeitigen Ausgestaltung der EU-Agrarpolitik bis zum Jahr 2020. Im Hauptszenario eines Auslaufens der Quotenregelung in 2015 ergibt sich in der EU-27 eine Produktionsausdehnung von 3.0% und ein durchschnittlicher Verfall der Rohmilchpreise um 7.2%. Der resultierende Preisrückgang bei Butter ist abhängig davon, ob Exporterstattungen zur Abfederung des Preisdrucks eingesetzt werden. Die Ergebnisse werden stark von der Spezifikation der Quotenrenten geprägt, während das Bild auf Mitgliedsländerebene auch von der Intra-EU-Preistransmission beeinflusst wird. Im Hauptszenario mit Exporterstattungen kommt es zu einer deutlichen Umverteilung von der Landwirtschaft und, weitaus weniger gewichtig, von Steuerzahlern zur Molkereiwirtschaft und Endverbrauchern. Der resultierende Wohlfahrtsgewinn ist klein, würde aber ansteigen, wenn die Quoten in einer Situation ohne Exporterstattungen auslaufen würden (Quelle: Verlag).
Keywords: 330; Milchpolitik; Partielles Gleichgewicht; EU-Agrarpolitik; Wirkungsanalyse; EU-Staaten